THE STUDY OF CURRENT PATTERN, TIDES AND WAVES ON THE BEACHES VILLAGE PANGKE VILLAGERS MERAL KARIMUN DISTRICT RIAU ARCHIPELAGO PROVINCE - Sherly Ayunarita; Elizal '; Musrifin Ghalib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from February to March 2017 in Pelawan Beach of Riau Archipelago Province which aims to study the pattern of current, tides and wave characteristics of Pelawan Beach. The method used in this research was survey method. Determination of stations for data collection, in 3 stations with 3 sampling points. The results showed that the mean of current speed at high tide was 0,48 m/sec (Southeast and East) and mean of current speed at low tide 0,46 m/sec (West and Northwest). The tide in this area is mixed tide type with dominant of semi-diurnal, which occurs twice of high tide and twice of low tide in a day. Characteristics of the waves ( height, period, length and slope) is plunging and formed beach type. The depth of the waters is sloping and shallow, ranges from 1,1 to 2,0 m. Current and wave conditions in Pelawan Beach waters are safe for coastal activity around Pelawan Beach.Keywords : Current, Tides, Wave, Pelawan Beach